Analytical determination of shape singularities for three types of parallel manipulators. (July 2020) - Wu, Xiaoyong; Bai, Shaoping
Abstract: Singularity analysis is an important issue in mechanism design, as kinetostatic properties of a manipulator will undergo a sudden and dramatic change close to singular configurations. Architecture singularity is a type of singularity caused by a special architecture of a manipulator. In this work, a new approach is developed to find efficiently architectural singularity due to special platform shapes, or shape singularity for short. The new method is based on analytical formulation combined with detection of singularity with selected configurations. By this way, intensive calculation and equation solving are avoided and the shape singularity can be detected more efficiently. With the developed method, shape singularities are determined for three parallel manipulators, including 3-DOF planar and spatial parallel mechanisms, and the 6-DOF Stewart–Gough manipulator.